Experimental and thermal performance investigations on sensible storage based solar air heater. (October 2020) - Vijayan, S.; Arjunan, T.V.; Kumar, Anil; Matheswaran, M.M.
Highlights: Developed a solar air heater with corrugated absorber plate integrated with porous bed. Energy efficiency with packed bed varies from 20.35% to 50.92.% Exergy efficiency with packed bed +3.97% to −2.81% for the mass flow rates 0.0141 kg/s to 0.0872 kg/s. Solar collector with packed bed capable to deliver the hot air in the range of 45 to 60 °C –suitable for drying. Energy efficiency of the packed bed collector is 3 to 8% higher than the collector without packed bed. Abstract: The thermal performance of the solar collector for air heating purpose is investigated with and without packed bed through experimental and theoretical methods. A simple flat plate solar air heater was developed with 2m 2 corrugated absorber plate and integrated with porous pebble bed in the airflow path to act as a sensible heat storage medium. The experimental studies were carried out for different mass flow rates of air from 0.014 to 0.087 kg/s with the increment of 0.0095 kg/s. Steady-state theoretical models have been established to predict the thermal performance of the air heaters and the results indicated that they are well enough to predict the outlet air temperature with acceptable error percentage. The collector with packed bed storage medium is more efficient than without packed bed in terms of energy efficiency as well as in reducing temperature fluctuation of air at the outlet of the collector. The energy and exergy efficiency of the collector with packed bed veried from 20.35% to 50.92% and +3.97% to −2.807% for the airflow rates 0.014 kg/s to 0.087 kg/s respectively. Solar collectors with packed bed are capable to deliver the hot air in the range of 45 to 60 °C for a longer period and which can be preferred for achieving a better quality of the dried products as well as for space heating applications.